Valores sociais na mesa : comida cotidiana e festiva em Vila Bela da Santíssima Trindade - Fava, Bruna Mendes de (2015)
How the cooking and eating habits reveal social values in the community of Vila Bela da Santíssima Trindade, Mato Grosso is the question that guides this work. On this research bibliographical studies were done and visits during the saints parties in July to watch the festive food, and in December to observe the everyday food. Eight women were interviewed cooking in their homes on a daily basis and also eight women who are party cooks. Vila Bela in Mato Grosso was chosen because it is in the majority composed by descendants of African slaves, with unique history in terms of occupation and development. The main authors of the theoretical studies were Cascudo on the history of Brazilian food, Machado Pais with the sociology of everyday life and McCracken, Linares e Trindade, Miller, Barbosa, Douglas and Isherwood with the sociology of consumption. The study of vilabelenses food consumption was also studied, from the everyday and festive shopping and individual and collective choices, identity reflections of the community. It is also observed how the food of the community expressed the social values and power relations, checking that the power says of his people. Interviews and observations allowed us to understand the relationship between food and culture of the population, existing historical elements that justify the use of certain ingredients, dishes and community income. The cooking and eating habits reveal social values and at the same time express their power relations and hierarchies that can be look in the ways of serving the party.